Clinical outcomes and resource utilization after surgical resection with curative intent among patients with non‐small cell lung cancer treated with adjuvant therapies in a community oncology setting: A real‐world retrospective observational study. Issue 14 (24th May 2021) - Cai, Beilei; Fulcher, Nicole; Boyd, Marley; Spira, Alexander
Abstract: Aims: Adjuvant chemotherapy has been shown to improve survival in patients with completely resected early‐stage non‐small cell lung cancer (NSCLC). This study evaluated real‐world relapse rates and healthcare resource utilization in patients with stage II–IIIB NSCLC receiving adjuvant therapy in a community oncology setting after complete resection. Patients and Methods: The study included patients with stage II–IIIB NSCLC and complete resection receiving any adjuvant therapy during 06/2008–04/2017 at US Oncology Network clinics, with follow‐up through 04/2019. Primary endpoints were rate of relapse, time to relapse (TTR), disease‐free survival (DFS), overall survival (OS), and monthly emergency department (ED) visits and hospitalizations before and after relapse. Results: The study identified 456 patients; median age was 66 years, 50% were male. In patients with relapse (45.2%), median follow‐up was 31.7 months and median TTR was 13.7 months. Median DFS in the overall population was 42.9 months. Median OS was 82.4 months in the overall population and shorter in patients with relapse than without relapse (41.6 months vs. not reached, p  < 0.0001). Patients with relapse had significantly more monthly ED visits (mean [SD] 0.10 [0.24] vs. 0.03 [0.08], p  < 0.0001) and hospitalizations (mean [SD] 0.20 [0.43] vs. 0.05 [0.10], p  < 0.0001) following relapse than before relapse. Conclusions: Patients with stage II–IIIB NSCLC treated with adjuvant therapy after complete resection had high relapse rates, reduced survival, and significantly increased healthcare resource use when relapse occurred. New therapeutic options to reduce relapse rates in patients with early‐stage NSCLC could reduce healthcare utilization and costs. Abstract : This retrospective study evaluated real‐world relapse rates and healthcare resource utilization in patients with stage II–IIIB non‐small cell lung cancer receiving adjuvant therapy after complete resection in community‐based oncology practices. Patients had high relapse rates, reduced survival, and significantly increased healthcare resource use when relapse occurred.